The Role of You Tube in Improving Expository Text Writing Skills: The Perspective of Indonesian Language Teachers at SMA Negeri 1 Doloksanggul - Tuty Susianti Sihombing; Rudy; Dian Syahfitri (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2025)
This qualitative study aims to find out and describe in detail the importance of the role of YouTube media as a learning material and analyze the perspective of Indonesian Language teachers of SMA Negeri 1 Doloksanggul on the use of YouTube to improve their students’ skills in writing expository texts. This study can theoretically contribute to the development of theories in the fields of education, teaching, or humanities that are relevant and practically useful as a reference for future research with similar topics and to improve public understanding of the benefits of YouTube for expository text writing skills. The main data were obtained from the structured face-to- face interview with five respondents. By applying thematic analysis, the transcribed interview results were arranged and categorized based on relevant themes. The results show that YouTube plays an important role because it can be perceived as an interesting, effective, and creative media, however, teachers must be proactive in this regard. Thisstudy also suggests that the use of YouTube as a learning material for writing expository texts is considered effective because students are encouraged to argue, use more vocabulary, write texts systematically and are motivated. The results of the data analysis show that the obstacles often encountered are problems with the Internet network,school facilities, and distractions.